Oxidative stability of biodiesel blends derived from waste frying oils - Feroldi, Michael (2017)
The high cost of biodiesel production is mainly linked to the price of raw material.This factor has favored the use of alternative fats and oils such as those used in frying. Since biodiesel can be obtained from several vegetable and animal raw materials, the physicochemical characteristics of the fuel may vary considerably. One of these characteristics is the fatty acid composition. It directly affects the oxidative stability of biodiesel, which can be impaired when the fuel undergoes exposure to sunlight, metals, oxygen and high temperatures. In order to improve the oxidative stability of biodiesels produced from waste frying oil some studies involving blends of different raw materials have been carried out. In this sense, this work aimed to assess the characteristics resulting from the blending of soybean waste frying oil with other waste biodiesels in what concerns to oxidation. The blends of fatty materials were obtained by means of a 2² factorial design. The induction periods of biodiesel blends were enough to meet the ASTM D6751 standard. Swine fat was responsible for the increase in the induction period values.